Using SWAT to simulate crop yields and salinity levels in the North Fork River Basin, USA - Mittelstet, Aaron Ray; Storm, Daniel E.; Stoecker, Art L. (International Journal of Agricultural and Biological Engineering, 2015)
Crop yields and salinity levels in the North Fork of the Red River (North Fork River) basin, located in southwestern Oklahoma and the Texas Panhandle, were analyzed based on the diverse climate in the region. Saline irrigation water is a major problem in the basin. The Elm Fork Creek flows through salt deposits, making the creek and its receiving stream, the North Fork River, too saline to use for irrigation. This greatly reduces the number of hectares that can be utilized for agricultural crops within the basin. A baseline SWAT model was setup, calibrated and validated to simulate streamflow and wheat and cotton yields. The SWAT model and a regression equation were used to analyze variable weather impacts on crop yields and salinity levels. Using the weather generator WXGEN and 58 years of observed weather data, ten 50-year weather datasets were generated. Output from the weather generator was input into the calibrated SWAT model to simulate wheat and dryland and irrigated cotton yields for the ten weather scenarios. Using an empirical relationship between ionic strength and streamflow, salinity levels were estimated. Though the crop yields varied greatly from year to year, the yields were not significantly different over the 50-year simulation period. The electrical conductivity (EC, expressed in decisiemens per meter or dS/m) at the US Geological Survey gage station just downstream of the salt deposits was significantly different with levels ranging from 40 to 65 dS/m. Though the water in the Elm Fork is much too saline to use for irrigation, the water in the North Fork River may be used as long as the flow rates in the river are greater than 0.60 m3/s. In order to optimize the available cropland, a salinity control must be installed upstream of the salt deposits on the Elm Fork Creek.Keywords: salinity, SWAT, crop yield, wheat modeling, cotton modeling, Red RiverDOI: 10.3965/j.ijabe.20150803.950 Online first on [2015-03-17]Citation: Mittelstet A R, Storm D E, Stoecker A L. Using SWAT to simulate crop yields and salinity levels in the North Fork River Basin, USA. Int J Agric & Biol Eng, 2015; 8(3): 110－124.